Kur'an-ı Kerim'de Dâvûd ve Süleymân (A.S) Kıssaları - Kartal, Ataullah (My University, 2009)
Kıssa, Davud, Süleyman, Belkıs, Talut, Calut ÖZET KUR’ÂN-I KERÎM’DE DÂVÛD VE SÜLEYMAN (AS) KISSALARI Tezimizde Kur’ân kıssalarının hedeflediği tüm amaçları ortaya koyma ile birlikte, İslâmiyet ve Yahudilik’te büyük önem taşıyan Dâvûd (as) ile Süleyman (as)’ı tüm yönleriyle tanıma, bu iki peygamber hakkındaki haberleri analiz etmek sûreti ile doğru ve yanlış bilgileri ortaya koymaya çalıştık. Tezimiz üç bölümden oluşmaktadır: Birinci bölümde Kur’ân kıssaları hakkında verdik. Kıssa kelimesinin sözlük ve terim anlamı ile anlam ilişkisi olan diğer kelimeler, kıssaların önemi, özellikleri, amaçlarını işledik. Kur’ân kıssalarının vahiy kaynaklı olduğunu ispât ettik ve kıssaları tarihsel yorumlayanların iddialarının gerçek olmadığı üzerinde durduk. İkinci bölümde Dâvûd (as)’a kadarki İsrâîloğulları tarihini, Dâvûd (as) hakkında genel bilgi, peygamberlik öncesi ve sonrası dönemi, mucizelerini, kendisine verilen nimetleri ve Dâvûd (as)’la ilgili hadîsleri izâh ettik. Kur’ân ve Kitâb-ı Mukaddes’te geçen bu kıssayı anlatarak değerlendirmelerde bulunduk. Son olarak da bu kıssadan çıkarılabilecek mesajları anlattık. Üçüncü bölümde ise Süleyman (as) ile ilgili genel bilgi, peygamberlik ve hükümdârlığı, mucizelerini, kendisine verilen nimetleri ve Süleyman (as)’la ilgili hadîsleri izâh ettik. Kur’ân-ı Kerîm ve Kitâb-ı Mukaddes’te geçen bu kıssayı anlatarak değerlendirmelerde bulunduk. Son olarak da bu kıssadan çıkarılabilecek mesajları anlattık. ssa (Quranic stories), David, Solomon, The Queen of Saba, Saul, Goliath

STORIES OF THE PROPHETS DAVID AND SOLOMON IN THE QURAN We have aimed to introduce all the goals of the Quranic stories and also to know the Prophets David and Solomon in all aspects who have a great importance both in Judaism and Islam at the same time. Another intention is to analyse all the relevant information about these two messengers by exhibiting both reliable and unreliable sources. Our thesis consists of three parts: In the first section we informed the readers about the Quranic stories in general. We discussed different topics such as the general and terminological meanings of “qissa” (true stories told in the Quran), other closely related words, the importance of the stories, their characteristic features and goals. We managed to prove that the stories told in the Quran are all relevations from God and divine facts, and that although there are people who try to understand them exclusively from a historical point of view this cannot be accepted as it leads to incorrect assessments and misunderstandings. In the second section we examined the historical phase of the Israelites before the Prophet David and provided about him by explaining his life before and after his prophethood, his miracles, the blessings he was bestowed by Allah and the sayings of Mohammad about him. We reached certain conceptions through scrutinizing his life both in The Old Testament and the Quran. Finally we submitted the messages which can be inferred from the relevant story. In the final chapter we informed the readers about the Prophet Solomon and explained his prophethood, kingship, miracles, bestowments and the Mohammadic sayings about him. We reached certain conceptions through scrutinizing his life both in The Old Testament and The Quran as we did it about his father. As a final stage we submitted the messages which are implied in the related story.
Keywords: Ayetler Ve Sureler_Kur’an-ı Kerim; İslam Dini_Tefsir; Kur’an-ı Kerim; Peygamberler_Hz. Davud; Peygamberler_Hz. Süleyman